The Decreasing of Debris Index in Toddlers with Mother Guiding on Posyandu - Silvia Prasetyowati; Bambang Hadi Sugito (Alliance oh Health Activists (AloHA), 2019)
The role of parents is indispensable in guiding, understanding, reminding and providing facilities to children in order to maintain their oral hygiene. The mother guiding model aims to change the knowledge, attitudes and skills of mother in decreasing toddler index debris. The purpose of this study was to analyze the model of guiding in mothers to decrease toddler plaque index. The type of research was quasi-experimental analysis. The research target was all mothers of toddlers who had children aged 3-5 years. Data collection method used questionnaires and oral hygiene status sheets. Analysis data technique used Mcnemar statistical test. The results showed a significant difference between maternal knowledge before and after guiding. There were significant differences between maternal attitudes before and after guiding. There were significant differences between mother's brushingtooth skills before and after guiding. There is a difference in mean of debris index for toddlers between before and after mother guiding. Keywords: Debris index, Toddler, Mother guiding